Incidence, Persistence, and Factors Associated With HPV Infection Among Male Adolescents With and Without Perinatally Acquired HIV Infection. (15th December 2020) - Gatechompol, Sivaporn; Teeratakulpisarn, Nipat; Wittawatmongkol, Orasri; Teeraananchai, Sirinya; Kerr, Stephen J.; Chalermchockcharoenkit, Amphan; Thamkhantho, Manopchai; Singtoroj, Thida; Phanuphak, Nittaya; Sohn, Annette H.; Chokephaibulkit, Kulkanya
Abstract : Background: Infection with high-risk human papillomavirus (HR-HPV) has been shown to be more prevalent and persistent in female adolescents with HIV. However, data among male adolescents with perinatally acquired HIV (PHIV) are limited. Setting: We investigated the incidence and persistence of HR-HPV in anogenital compartments and associated factors among PHIV in comparison to HIV-uninfected (HU) male adolescents in Thailand. Methods: PHIV and HU males aged 12–24 years were enrolled. At baseline and 3 subsequent annual visits, specimens from the scrotum, penis, and anal area were obtained for HPV and other testing. Results: From June 2013 to October 2017, 49 PHIV and 47 HU male adolescents with a median age of 18 (interquartile range 17–20) years were enrolled. PHIV had higher incidence of any HR-HPV infection than HU adolescents 33.05 [95% confidence interval (CI): 20.82 to 52.46] vs. 15.73 [95% CI: 8.18 to 30.22] per 100 person-years, P = 0.04. The persistence of any HR-HPV genotypes (detected at ≥2 annual visits) was not different by group (PHIV 27% vs. HU 23%, P = 0.75). Having ≥3 sex partners in past 6 months (adjusted prevalence ratio 2.39, 95% CI: 1.14 to 5.05; P = 0.02) and co-infection with other sexually transmitted infections (syphilis, chlamydia, and/or gonorrhea) were associated with persistent HR-HPV infection (adjusted prevalence ratio 6.21, 95% CI: 2.87 to 13.41; P < 0.001). Conclusions: Thai PHIV male adolescents had a higher incidence of HR-HPV infection than those without HIV. Having multiple sex partners and co-infection with sexually transmitted infections was associated with persistent HR-HPV infection. These data demonstrate the need to prioritize PHIV male adolescents in routine and catch-up HPV vaccination programs.